Effect of dietary supplementation of Nannochloropsis on gene expression and metabolic profile of immune and antioxidant markers in growing Barki lambs - Ebissy, E; El-Sayed, A; Ateya, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of the current study was to elaborate the effect of dietary supplementation of Nannochloropsis on gene expression and metabolic profile of immune and antioxidant markers in growing Barki lambs. Sixty apparently healthy growing Barki lambs were enrolled in this study. Lambs were randomly allocated into two equal groups (30 lambs each). The first group considered control group, whereas the second group supplemented with commercially available Nannochloropsis powder for subsequent 30 days. Supplementation of growing lambs with Nannochloropsis could modulate gene expression profile of immune and antioxidant markers. Levels of immune (IL1B, IL2, Il6, IL8, RANTES, NFKB, MASP2 and TNFα) and antioxidant (SOD3, GPX4, PRDX2, and Nrf2) genes expression were significantly up-regulated in lambs supplemented with Nannochloropsis at day 30 than control and day 15. There was a significant (p < 0.05) increase in the serum concentrations of SOD, CAT, TAC, GPx, NO, GSH, lysozyme activity, TNF-α, IL1, IL-6 and IgA with significant decrease in MDA level in supplemented group in relation to control ones. While IgG and IgM levels were not significantly (P > 0.05) differed among the tested groups. The results herein confirm that there was profound immunological, antioxidant alterations associated with dietary supplementation of Nannochloropsis in growing Barki lambs. Gene expression and serum profiles may serve as stand-in markers for immunological status monitoring and the development of an efficient management strategy for enhancing the health of growing Barki lambs.